Acid-free polarizer pressure-sensitive adhesive and preparation method thereof
Through the acid-free polarizer pressure-sensitive adhesive formula and preparation method, the acid corrosion and insufficient performance of polarizer pressure-sensitive adhesive in the prior art are solved, and high-performance and long-life pressure-sensitive adhesives are realized, which are suitable for a wide range of applications.
Patent Information
- Application Number
- CN202310891595.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The existing polarizer pressure-sensitive adhesives have the corrosion effect of acidic substances on the polarizer, and the bonding performance, water resistance, weather resistance and high temperature and humidity resistance are insufficient, resulting in a short service life.
Acid-free polarizer pressure-sensitive adhesive formula, including acrylate copolymers, end-hydroxyvinyl hyperbranched poly(urethane-amine), terpene resin, 3,3'-diamino-4,4'-difluoro Diphenylsulfone, polythiophene with alcoholamine groups on the side chain and initiator, form a pressure-sensitive adhesive with excellent bonding properties, water resistance and weather resistance through reasonable formulation and preparation methods.
It achieves improvements in bonding performance, water resistance, weather resistance and anti-static properties, extends service life, and reduces production costs and energy consumption, making it suitable for continuous large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive products, and in particular to an acid-free polarizer pressure-sensitive adhesive and a preparation method thereof. Background Art
[0002] With the increasing popularity of various electronic display devices, mankind has entered a new "screen era". Liquid crystal displays have been widely used in mobile phones, computers, LCD TVs, automotive electronics, medical equipment, instrumentation and other fields. Polarizers are an important component of liquid crystal displays, and the imaging of liquid crystal displays must rely on polarizers. During use, polarizers need to be attached to the glass substrate of the liquid crystal display through pressure-sensitive adhesives. The performance of polarizer pressure-sensitive adhesives directly affects the use effect and service life of polarizers. It can be seen that it is particularly important to develop polarizer pressure-sensitive adhesives with excellent comprehensive performance and performance stability.
[0003] Common polarizer pressure-sensitive adhesives are acrylic pressure-sensitive adhesives. Since these pressure-sensitive adhesives contain acidic substances, they have a certain corrosive effect on polarizers, affecting the use effect and service life of polarizers. Other types of polarizer pressure-sensitive adhesives on the market also have more or less defects such as limited bonding performance, water resistance and weather resistance, and the high temperature and high humidity resistance and light transmittance need to be further improved.
[0004] For example, Chinese invention patent document CN102010672B discloses a UV-curable pressure-sensitive adhesive for LCD polarizer and a preparation method thereof; the adhesive comprises at least three substances in the following mass fractions: a. a weight average molecular weight of 100,000 to 1,000,000, and a dispersion degree M w / M n a. 30 to 60 parts of acrylate copolymer with a content of 3 to 10; b. 40 to 70 parts of UV-curable components, and the sum of a and b is 100 parts; c. Photoinitiator system, which is 0.5 to 6.5 parts compared with the sum of a and b of 100 parts. The invention avoids the use of thermal crosslinking agents and adopts UV crosslinking. The crosslinking process is fast, the production efficiency is high, and the crosslinking process is easier to control. The curing time only takes 0.5 to 3 minutes, avoiding the long thermal crosslinking process of the traditional process. The prepared pressure-sensitive adhesive can meet the actual use requirements in terms of performance (initial adhesion, peel strength). The initial adhesion can be greater than that of a No. 14 ball, and the peel strength can be greater than 9.81N / 25mm. However, it contains acidic monomer acrylic acid, which has a certain corrosive effect on polarizers and liquid crystal displays.
[0005] It can be seen that the development of an acid-free polarizer pressure-sensitive adhesive with good bonding performance, water resistance and weather resistance, good high temperature and humidity resistance and light transmittance, and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the polarizer pressure-sensitive adhesive field. Summary of the invention
[0006] The main purpose of the present invention is to provide an acid-free polarizer pressure-sensitive adhesive having good bonding performance, water resistance and weather resistance, good high temperature and humidity resistance and light transmittance, and long service life, and a preparation method thereof.
[0007] To achieve the above purpose, the present invention provides an acid-free polarizer pressure-sensitive adhesive, which comprises the following components in parts by weight: 30-40 parts of an acrylate copolymer, 2-4 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 3-5 parts of a terpene resin, 2-4 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.8-1.5 parts of a polythiophene having an alcoholamine group on the side chain, 0.8-1.2 parts of an initiator, and 30-50 parts of a solvent.
[0008] Preferably, the acrylic copolymer is made of the following raw materials in parts by weight: 18-32 parts of soft monomer, 8-10 parts of hard monomer, 1-3 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.2-0.5 parts of azobisisobutyronitrile, and 20-30 parts of solvent.
[0009] Preferably, the solvent is one or more of butanone, toluene, ethyl acetate, and N,N-dimethylformamide.
[0010] Preferably, the soft monomer is one or more of butyl acrylate, lauryl acrylate, n-octyl acrylate, ethyl acrylate, and isooctyl acrylate.
[0011] Preferably, the hard monomer is one or more of acrylonitrile, styrene, methyl methacrylate, isobornyl methacrylate, tert-butyl acrylate, ethyl methacrylate, and n-butyl methacrylate.
[0012] Preferably, the method for preparing the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting at 60-75° C. in an inert gas atmosphere for 4-6 hours, and cooling the material after the reaction to obtain the acrylic copolymer.
[0013] Preferably, the inert gas is any one of nitrogen, helium, neon and argon.
[0014] Preferably, there is no special requirement for the source of the terminal hydroxyl vinyl hyperbranched poly(urethane-amine). In one embodiment of the present invention, the terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) with a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of Example 1 in Chinese invention patent CN106519158B.
[0015] Preferably, the terpene resin is terpene resin T80.
[0016] Preferably, there is no special requirement for the source of the polythiophene having an amine group on the side chain. In one embodiment of the present invention, the polythiophene having an amine group on the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9.
[0017] Preferably, the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptylnitrile.
[0018] Another object of the present invention is to provide a method for preparing the acid-free polarizer pressure-sensitive adhesive, comprising the following steps: mixing the components of the acid-free polarizer pressure-sensitive adhesive evenly by weight, standing and defoaming to obtain a pressure-sensitive adhesive coating liquid, then evenly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying and attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive.
[0019] Preferably, the drying temperature is 100-115° C., and the time is 2-4 minutes; the aging temperature is 30-40° C., and the time is 1-2 days.
[0020] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The method for preparing the acid-free polarizer pressure-sensitive adhesive disclosed in the present invention only requires the raw materials to be mixed evenly and then coated, dried and aged. No special equipment is required, and no modification of the existing production line is required. The method has low capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.
[0021] (2) The acid-free polarizer pressure-sensitive adhesive disclosed in the present invention comprises the following components by weight: 30-40 parts of acrylate copolymer, 2-4 parts of terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 3-5 parts of terpene resin, 2-4 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.8-1.5 parts of polythiophene with alcoholamine groups on the side chain, 0.8-1.2 parts of initiator, and 30-50 parts of solvent. Through the interaction between the components, the pressure-sensitive adhesive has good bonding performance, water resistance and weather resistance, high temperature and high humidity resistance and light transmittance, and long service life.
[0022] (3) The acid-free polarizer pressure-sensitive adhesive disclosed in the present invention, the acrylic copolymer is made of the following raw materials in parts by weight: 18-32 parts of soft monomer, 8-10 parts of hard monomer, 1-3 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.2-0.5 parts of azobisisobutyronitrile, and 20-30 parts of solvent. By rationally selecting the raw material formula, the formed copolymer can better synergize with other components, improve the bonding performance, water resistance and weather resistance of the pressure-sensitive adhesive, improve the high temperature and high humidity resistance and light transmittance, and extend its service life.
[0023] (4) The acid-free polarizer pressure-sensitive adhesive disclosed in the present invention, by adding polythiophene having an amine group on the side chain, can give the pressure-sensitive adhesive better antistatic properties. In addition, due to the presence of the amine group, the compatibility between the pressure-sensitive adhesive and other components is good, thereby improving the performance stability of the pressure-sensitive adhesive and extending its service life.
[0024] (5) The acid-free polarizer pressure-sensitive adhesive disclosed in the present invention introduces hyperbranched poly(urethane-amine), zwitterionic salt, triazone, ester group, terpene resin, difluorodiphenyl sulfone, alcoholamine group and polythiophene structure into the pressure-sensitive adhesive structure through the reasonable selection of components and raw materials. These structures further improve the comprehensive physical properties and performance stability of the pressure-sensitive adhesive under the multiple effects of electronic effect, steric effect and conjugation effect, so that the product has good bonding performance, water resistance and weather resistance, high temperature and high humidity resistance and light transmittance, and long service life. DETAILED DESCRIPTION
[0025] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0026] An acid-free polarizing film pressure-sensitive adhesive comprises the following components, measured by weight: 30 parts of an acrylate copolymer, 2 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 3 parts of a terpene resin, 2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.8 parts of a polythiophene having an alcoholamine group on the side chain, 0.8 parts of an initiator, and 30 parts of a solvent.
[0027] The acrylic copolymer is made of the following raw materials in parts by weight: 18 parts of soft monomer, 8 parts of hard monomer, 1 part of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.2 parts of azobisisobutyronitrile, and 20 parts of solvent; the solvent is butanone; the soft monomer is butyl acrylate; and the hard monomer is acrylonitrile.
[0028] The preparation method of the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting them at 60° C. for 4 hours in an inert gas atmosphere, and cooling the material after the reaction to obtain the acrylic copolymer; the inert gas is nitrogen.
[0029] The terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) having a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of implementation case 1 in Chinese invention patent CN106519158B; the terpene resin is terpene resin T80; the polythiophene having an alcoholamine group in the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9; and the initiator is azobisisobutyronitrile.
[0030] A preparation method of the acid-free polarizer pressure-sensitive adhesive comprises the following steps: uniformly mixing the components of the acid-free polarizer pressure-sensitive adhesive according to parts by weight, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, and then uniformly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying, attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive; the drying temperature is 100° C. and the time is 2 minutes; the aging process temperature is 30° C. and the time is 1 day. Example 2
[0031] The invention discloses an acid-free polarizing film pressure-sensitive adhesive, comprising the following components by weight: 33 parts of an acrylic copolymer, 2.5 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 3.5 parts of a terpene resin, 2.5 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1 part of a polythiophene having an alcoholamine group on a side chain, 0.9 parts of an initiator, and 35 parts of a solvent.
[0032] The acrylic copolymer is made of the following raw materials in parts by weight: 22 parts of soft monomer, 8.5 parts of hard monomer, 1.5 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3.5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.3 parts of azobisisobutyronitrile, and 23 parts of solvent; the solvent is toluene; the soft monomer is lauryl acrylate; and the hard monomer is styrene.
[0033] The preparation method of the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting them at 65° C. for 4.5 hours in an inert gas atmosphere, and cooling and discharging the materials after the reaction to obtain the acrylic copolymer; the inert gas is helium.
[0034] The terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) having a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of implementation case 1 in Chinese invention patent CN106519158B; the terpene resin is terpene resin T80; the polythiophene having an alcoholamine group in the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9; and the initiator is benzoyl peroxide.
[0035] A preparation method of the acid-free polarizer pressure-sensitive adhesive comprises the following steps: uniformly mixing the components of the acid-free polarizer pressure-sensitive adhesive according to parts by weight, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, and then uniformly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying, attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive; the drying temperature is 105° C., and the time is 2.5 min; the aging process temperature is 32° C., and the time is 1.2 days. Example 3
[0036] An acid-free polarizing film pressure-sensitive adhesive comprises the following components, measured by weight: 35 parts of an acrylate copolymer, 3 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 4 parts of a terpene resin, 3 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1.2 parts of a polythiophene having an alcoholamine group on the side chain, 1 part of an initiator, and 40 parts of a solvent.
[0037] The acrylic copolymer is made of the following raw materials in parts by weight: 25 parts of soft monomer, 9 parts of hard monomer, 2 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 4 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.35 parts of azobisisobutyronitrile, and 25 parts of solvent; the solvent is ethyl acetate; the soft monomer is n-octyl acrylate; and the hard monomer is methyl methacrylate.
[0038] The preparation method of the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting them at 68° C. for 5 hours in an inert gas atmosphere, and cooling the material after the reaction to obtain the acrylic copolymer; the inert gas is neon.
[0039] The terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) having a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of implementation case 1 in Chinese invention patent CN106519158B; the terpene resin is terpene resin T80; the polythiophene having an alcoholamine group in the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9; and the initiator is azobisisoheptonitrile.
[0040] A preparation method of the acid-free polarizer pressure-sensitive adhesive comprises the following steps: uniformly mixing the components of the acid-free polarizer pressure-sensitive adhesive according to parts by weight, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, and then uniformly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying, attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive; the drying temperature is 110° C., and the time is 3 minutes; the aging process temperature is 35° C., and the time is 1.5 days. Example 4
[0041] An acid-free polarizing film pressure-sensitive adhesive comprises the following components, measured by weight: 38 parts of an acrylate copolymer, 3.5 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 4.5 parts of a terpene resin, 3.5 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1.3 parts of a polythiophene having an alcoholamine group on the side chain, 1.1 parts of an initiator, and 45 parts of a solvent.
[0042] The acrylic copolymer is made of the following raw materials in parts by weight: 30 parts of soft monomer, 9.5 parts of hard monomer, 2.5 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 4.5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.45 parts of azobisisobutyronitrile, and 28 parts of solvent; The solvent is N,N-dimethylformamide; the soft monomer is a mixture of butyl acrylate, lauryl acrylate, n-octyl acrylate, ethyl acrylate, and isooctyl acrylate in a mass ratio of 1:2:1:3:2; the hard monomer is a mixture of acrylonitrile, styrene, methyl methacrylate, isobornyl methacrylate, tert-butyl acrylate, ethyl methacrylate, and n-butyl methacrylate in a mass ratio of 1:3:1:2:1:1:3.
[0043] The preparation method of the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting them at 73° C. in an inert gas atmosphere for 5.5 hours, and cooling the material after the reaction to obtain the acrylic copolymer; the inert gas is argon.
[0044] The terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) having a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of implementation case 1 in Chinese invention patent CN106519158B; the terpene resin is terpene resin T80; the polythiophene having an alcoholamine group in the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9; the initiator is a mixture of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptonitrile in a mass ratio of 1:3:2.
[0045] A preparation method of the acid-free polarizer pressure-sensitive adhesive comprises the following steps: uniformly mixing the components of the acid-free polarizer pressure-sensitive adhesive according to parts by weight, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, and then uniformly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying, attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive; the drying temperature is 113° C., and the time is 3.5 min; the aging process temperature is 38° C., and the time is 1.8 days. Example 5
[0046] An acid-free polarizing film pressure-sensitive adhesive comprises the following components, measured by weight: 40 parts of an acrylate copolymer, 4 parts of a terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 5 parts of a terpene resin, 4 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1.5 parts of a polythiophene having an alcoholamine group on the side chain, 1.2 parts of an initiator, and 50 parts of a solvent.
[0047] The acrylic copolymer is made of the following raw materials in parts by weight: 32 parts of soft monomer, 10 parts of hard monomer, 3 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.5 parts of azobisisobutyronitrile, and 30 parts of solvent; the solvent is butanone; the soft monomer is isooctyl acrylate; and the hard monomer is isobornyl methacrylate.
[0048] The preparation method of the acrylic copolymer comprises the following steps: uniformly mixing the raw materials by weight, stirring and reacting them at 75° C. for 6 hours in an inert gas atmosphere, and cooling and discharging the materials after the reaction to obtain the acrylic copolymer; the inert gas is nitrogen.
[0049] The terminal hydroxyl vinyl hyperbranched poly(urethane-amine) is a hyperbranched poly(urethane-amine) having a hydroxyl terminal group and a vinyl internal branching unit, and is prepared according to the method of implementation case 1 in Chinese invention patent CN106519158B; the terpene resin is terpene resin T80; the polythiophene having an alcoholamine group in the side chain is prepared according to the method of Example 2 in Chinese invention patent document CN201610225149.9; and the initiator is azobisisobutyronitrile.
[0050] A preparation method of the acid-free polarizer pressure-sensitive adhesive comprises the following steps: uniformly mixing the components of the acid-free polarizer pressure-sensitive adhesive according to parts by weight, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, and then uniformly coating the pressure-sensitive adhesive coating liquid on the surface of the polarizer, drying, attaching a release film, and then performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive; the drying temperature is 115° C. and the time is 4 minutes; the aging process temperature is 40° C. and the time is 2 days.
[0051] Comparative Example 1 The present invention provides an acid-free polarizer pressure-sensitive adhesive, the formula and preparation method of which are similar to those of Example 1, except that 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt are not added.
[0052] Comparative Example 2 The present invention provides an acid-free polarizer pressure-sensitive adhesive, the formula and preparation method of which are similar to those of Example 1, except that terminal hydroxyl vinyl hyperbranched poly(urethane-amine) and bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione are not added.
[0053] In order to further illustrate the unexpected beneficial technical effects of the acid-free polarizer pressure-sensitive adhesive involved in the embodiments of the present application, the acid-free polarizer pressure-sensitive adhesive prepared in each group of Examples 1-5 and Comparative Examples 1-2 was tested for relevant performances. The test results are shown in Table 1. During the preparation of the test samples, the dry adhesive thickness of each pressure-sensitive adhesive was controlled to be 10 μm. The test method is as follows: (1) Peel force test: Cut the pressure-sensitive adhesive into 300 × 25 mm size, remove the release film, and stick the pressure-sensitive adhesive to the glass surface. Use an electronic universal testing machine (model: AGS-X) to test the pressure-sensitive adhesive at an angle of 180 。 The peeling test was carried out under the conditions of 300 mm / min tensile speed.
[0054] (2) Adhesive layer resistance test: Cut the pressure-sensitive adhesive into 12 × 12 mm size, remove the release film, and test the adhesive surface resistance on a high resistance meter (model: SME-8310).
[0055] (3) High temperature and high humidity test: Cut the pressure-sensitive adhesive into 6×10 mm size, remove the release film, stick the pressure-sensitive adhesive on the glass surface, and put it into a programmable constant temperature and humidity test box. After 85°C, 90% RH×500h, observe whether the pressure-sensitive adhesive on the glass surface has wrinkles, detachment, or bubbles. If not, it is judged as OK; if so, it is judged as NG.
[0056] (4) High temperature and high humidity residual performance: Cut the pressure-sensitive adhesive into samples of 6 cm × 10 cm in size, remove the release film, and adhere to the glass surface to ensure that there are no bubbles. Place it in a programmable constant temperature and humidity test chamber (model: WHTH-150L-40-880) at a temperature of 60°C and a humidity of 90% RH for 7 days. Finally, remove the pressure-sensitive adhesive and observe whether there is any residue on the glass surface under a three-wavelength lamp. Among them, ○ indicates no residue; △ indicates slight residue; and × indicates obvious residue.
[0057]
[0058] It can be seen from Table 1 that the acid-free polarizer pressure-sensitive adhesive prepared in the embodiment of the present invention has better bonding performance, high temperature and humidity resistance and antistatic performance, and there is no residual adhesive under high temperature and high humidity conditions. The addition of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, terminal hydroxyl vinyl hyperbranched poly(urethane-amine) and bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is beneficial to improving the above properties.
[0059] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. An acid-free polarizer pressure-sensitive adhesive, characterized in that: The invention comprises the following components by weight: 30-40 parts of acrylic copolymer, 2-4 parts of terminal hydroxyl vinyl hyperbranched poly(urethane-amine), 3-5 parts of terpene resin, 2-4 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.8-1.5 parts of polythiophene having an alcoholamine group on the side chain, 0.8-1.2 parts of initiator and 30-50 parts of solvent.
2. The acid-free polarizer pressure-sensitive adhesive according to claim 1, characterized in that: The acrylic ester copolymer is made of the following raw materials in parts by weight: 18-32 parts of soft monomer, 8-10 parts of hard monomer, 1-3 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-5 parts of bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.2-0.5 parts of azobisisobutyronitrile and 20-30 parts of solvent.
3. The acid-free polarizer pressure-sensitive adhesive according to claim 2, characterized in that: The solvent is one or more of butanone, toluene, ethyl acetate and N,N-dimethylformamide.
4. The acid-free polarizer pressure-sensitive adhesive according to claim 2, characterized in that: The soft monomer is one or more of butyl acrylate, lauryl acrylate, n-octyl acrylate, ethyl acrylate, and isooctyl acrylate.
5. The acid-free polarizer pressure-sensitive adhesive according to claim 2, characterized in that: The hard monomer is one or more of acrylonitrile, styrene, methyl methacrylate, isobornyl methacrylate, tert-butyl acrylate, ethyl methacrylate, and n-butyl methacrylate.
6. The acid-free polarizer pressure-sensitive adhesive according to claim 2, characterized in that: The preparation method of the acrylic ester copolymer comprises the following steps: mixing the raw materials uniformly by weight, stirring and reacting for 4-6 hours at 60-75° C. in an inert gas atmosphere, and cooling and discharging the material after the reaction to obtain the acrylic ester copolymer.
7. The acid-free polarizer pressure-sensitive adhesive according to claim 2, characterized in that: The inert gas is any one of nitrogen, helium, neon and argon.
8. The acid-free polarizer pressure-sensitive adhesive according to claim 1, characterized in that: The terpene resin is terpene resin T80; the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptylnitrile.
9. A method for preparing the acid-free polarizer pressure-sensitive adhesive according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing various components of an acid-free polarizer pressure-sensitive adhesive according to weight parts, standing to defoam, obtaining a pressure-sensitive adhesive coating liquid, uniformly coating the pressure-sensitive adhesive coating liquid on the surface of a polarizer, drying, attaching a release film, and performing a aging process to obtain the acid-free polarizer pressure-sensitive adhesive.
10. The method for preparing the acid-free polarizer pressure-sensitive adhesive according to claim 9, characterized in that: The drying temperature is 100-115° C., and the time is 2-4 minutes; the aging temperature is 30-40° C., and the time is 1-2 days.
Citation Information
Patent Citations
UV (Ultraviolet)-cured pressure-sensitive adhesive for LCD (Liquid Crystal Display) polarizer and preparation method thereof
CN102010672B
A method for preparing hyperbranched poly(urethane-amine) with hydroxyl end groups and vinyl internal branching units.
CN106519158B
Method for preparing high-strength heat-resistant silicon resin modified acrylic ester pressure-sensitive adhesive
CN101979454A
Polythiophene with side chain containing hydrophilic group, and preparation method thereof
CN105860033A
Environment-friendly conductive coating material and preparation method thereof
CN113773740A
